PENGARUH EKSTRAK DIKLOROMETAN JAHE (Zinger officinale Roscoe) TERHADAP PENGIKATAN TOKSIN KOLERA B-SUBUNIT CONJUGASI (FITC) PADA RESEPTOR SEL HIBRIDOMA LV DAN CACO-2 - Radiati L E; Nabet P Franck; Nabet B; Capiaumont J; Fardiaz D; Zakaria R F; I Sudirman; Hariyadi R D (Jurnal Teknologi dan Industri Pangan, 2003)
Cholera toxin is main factor that responsibility of watery diarrhea. The objectives of this investigation was to study the effect of ginger extract (GDE) in blocking cholera toxin binding to receptors of LV hybridome and Caco-2 cells. Analysis of toxin binding by flow cytometry of 0-5 Ã†â€™ÃƒÂg/ml of B-FITC conjugated cholera toxin to 105 cells/ml of LV hybridome and Caco-2 cells in RPMI, at 4Ã¢â‚¬Å¾aC for one hour showed that specific interaction of B-FITC by 44,44 Ã¢â‚¬Å¾b 3,49 percent to LV hybridome and by 94,58Ã¢â‚¬Å¾b 1,83 percent to Caco-2 cells. A total of 105 cells/ml of hybridome and Caco-2 cells were incubated with 0-5 Ã†â€™ÃƒÂg/ml toxin B-FITC and 25 or 50 Ã†â€™ÃƒÂg/ml GDE in RPMI, at 4Ã¢â‚¬Å¾aC for one hour showed that the addition of GDE inhibited the toxin binding. The binding inhibition respectively were 4.76-15.66 and 12.55-24.60 percent to Caco-2 cells, and 3.55-17.95 and 3.58-27.83 percent to hybridome cells. The inhibition on the toxin binding may be due to modification of the receptor by GDE or interaction of GDE with the toxin.Key words :  Hibridoma LV, Caco2, ekstrak diklorometan jahe,  and  toksin kolera B-FITC